+0  
 
+2
154
6
avatar+409 

If the parabola \(y_1=x^2+2x+7\)and the line \(y_2=6x+b\) intersect at only one point, what is the value of b?

michaelcai  Jul 17, 2017

Best Answer 

 #2
avatar+26322 
+2

The straight line must be tangent to the parabola.

 

Equate the two functions:

 

\(x^2+2x+7=6x+b\\x^2-4x+7-b=0\\\)

 

The discriminant must be zero if there is to be a single solution, so

 

\((-4)^2-4(7-b)=0\\-12+4b=0\\b=3\)

Alan  Jul 17, 2017
Sort: 

5+0 Answers

 #1
avatar+27 
0

I would assume that only a straight verticle line can intercept with a parabola.

DeadRight  Jul 17, 2017
 #2
avatar+26322 
+2
Best Answer

The straight line must be tangent to the parabola.

 

Equate the two functions:

 

\(x^2+2x+7=6x+b\\x^2-4x+7-b=0\\\)

 

The discriminant must be zero if there is to be a single solution, so

 

\((-4)^2-4(7-b)=0\\-12+4b=0\\b=3\)

Alan  Jul 17, 2017
 #4
avatar+27 
+1

I'm abit confused. Can you explained what happened after: "The discriminant must be zero if there is to be a single solution, so"

 

Why -4? 

DeadRight  Jul 18, 2017
 #3
avatar+78575 
+2

 

Here's another approach

 

If a line intersects a parabola at only one point, it is tangent to the parabola at that point.

 

So....the slopes  are equal at that point

 

The slope of the parabola at any point is   2x + 2

 

The slope of the line is a constant, 6

 

Equate the slopes

 

2x + 2  = 6

 

2x  = 4

 

x = 2

 

So.....this is the value where the slopes are the same.....subbing this into  both functions gives us

 

(2)^2 + 2(2) + 7  = 6(2) + b

 

15  =  12 + b

 

b = 3

 

 

cool cool cool

CPhill  Jul 17, 2017
 #5
avatar+78575 
+1

 

Remember that in the Quadratic Formula the discriminant (the part under the square root ), b^2 - 4ac, gives us some info about the solutions we can expect

 

If the discriminant evaluates to 0, it means that we have a "double root", i.e., only one solution

 

And since we only want one solution point in this problem -  the tangent point of the line to the parabola - we can see what value of "b" gives us a discriminant of 0

 

So...  using   x^2 - 4x + 7 - b = 0   let's change "b"  to "m"  so that we don't get it confused wih the "b" in the quadratic formula

 

So we have   x^2 - 4x + 7 - m = 0

 

And in the quadratic formula, let    a = 1, b = -4 and  c = 7 - m

 

So....  the discriminant becomes   b^2 - 4ac  →    (-4)^2 - 4(1)(7 - m)

 

Now....set this to 0 and solve for "m"

 

 (-4)^2 - 4(1)(7 - m) = 0    simplify

 

16- 28 + 4m  =  0

 

-12 + 4m = 0

 

4m = 12

 

m = 3

 

So.....the "m" - or in this case, the "b" - that gives us a single solution is 3

 

 

cool cool cool 

CPhill  Jul 18, 2017
edited by CPhill  Jul 18, 2017
edited by CPhill  Jul 18, 2017

7 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details